Mendefinisikan Pembangunan Perumahan Swadaya Secara Berkelanjutan - Tyas, Wido Prananing (Semarang State University, 2006)
Abstract: Self-help housing is the major type of housing in Indonesia; it's reached about 85 % of total housing. As the importance of self-help housing, a special attention should be given to fulfill this basic type of housing, especially the sustainability aspect of self help housing development. Economic, social and physical environment are important parameters for sustainable self-help housing development.Abstrak: Perumahan swadaya menjadi mayoritas bentuk dari bentuk pembangunan perumahan di Indonesia, yaitu mencapai angka 85 %. Mengingat pentingnya perumahan swadaya ini, perhatian akan bentuk perumahan ini perlu ditingkatkan. Aspek ekonomi, sosial dan fisik lingk:mgan menjadi parameter penting perumahan swadaya agar dapat berkelanjutan.